2014
DOI: 10.1159/000357446
|View full text |Cite
|
Sign up to set email alerts
|

A Herlyn-Werner-Wunderlich Syndrome Variant with Ipsilateral Renal Absence and a Contralateral Duplex Collecting System in a 26-Year-Old Female

Abstract: Herlyn-Werner-Wunderlich syndrome (HWWS) is a müllerian duct anomaly typically associated with a uterus didelphys with two cervices and two vaginas, one of which is obstructed. A remarkable case of HWWS with contralateral duplex kidneys and duplication of ureters is described, which, to our knowledge, is a rarely reported variant to date. For this congenital anomaly, a strong suspicion and knowledge of HWWS are essential for a precise diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…The association of uterus didelphys with an obstructed hemivagina is explained by a defect in embryogenesis at the eighth week of gestation affecting the mesonephric and Müllerian ducts, in which there is non-fusion of Müllerian ducts or failed resorption of the uterine/vaginal septum 1 . Other defects which can be found include renal dysplasia, duplication of the kidneys and ureters 11,12 , ectopic ureter, as well as high-riding aortic bifurcation, IVC duplication, intestinal malrotation 13 and ovarian malposition. Renal agenesis predicts an ipsilateral obstructive Müllerian duct abnormality 50% of the time and is ipsilateral to the dilated uterine cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The association of uterus didelphys with an obstructed hemivagina is explained by a defect in embryogenesis at the eighth week of gestation affecting the mesonephric and Müllerian ducts, in which there is non-fusion of Müllerian ducts or failed resorption of the uterine/vaginal septum 1 . Other defects which can be found include renal dysplasia, duplication of the kidneys and ureters 11,12 , ectopic ureter, as well as high-riding aortic bifurcation, IVC duplication, intestinal malrotation 13 and ovarian malposition. Renal agenesis predicts an ipsilateral obstructive Müllerian duct abnormality 50% of the time and is ipsilateral to the dilated uterine cavity.…”
Section: Discussionmentioning
confidence: 99%
“… 5 MRI and ultrasound are the most widely used diagnostic tools, with even 100% accuracy being reported for MRI because of its high accuracy and detailed elaboration of uterovaginal anatomy. 4 , 14 Several studies have reported the renal malformations in HWWS, including renal agenesis, multicystic dysplastic kidney, and absent kidney. However, the scoliosis among HWWS has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 Renal agenesis accompanies Müllerian duct abnormalities include the kidneys, fallopian tube, ovary, cervix, and upper vagina, all that generate from the same ureteric bud that fails to form correctly. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three characteristics of this syndrome include uterine didelphys (double uterus), hemivaginal obstruction, and ipsilateral kidney agenesis [ 6 , 7 ]. HWWs’ etiology and pathogenesis are unknown [ 8 - 10 ]. The incidence of HWWS is 0.6–10% of all Müllerian abnormalities (23%), 0.1 to 3.8% in the female population; up until 2011, only about 200 cases of HWWS have been documented worldwide [ 3 , 11 - 15 ].…”
Section: Introductionmentioning
confidence: 99%